Poválečné Spojené státy americké očima českého sociologa: Nepublikovaná reflexe Otakara Machotky v kontextech - Nešpor, Zdeněk R. (Lidé města, 2015)
One of the most significant Czech (social science) reflections of the United States was written by the sociologist Otakar Machotka (1899–1970) and was published in 1946. The author prepared an updated version of the chapter for publication reflecting the changes that American society underwent during World War II and its aftermath; however, this could not be published and thus remained unknown. This rare find in the archives of the unfinished, yet very significant manuscript as to its contents and methodology allowed it to be finally published; the editor supplemented Machotka’s work with an extensive contextual analysis. This article describes and analyses the development and character of Czech reflections of American society from the 19th c entury until the s econd half o f the 20th century, a tradition in which Machotka continued in and came to terms with, and which also stemmed off of Machotka’s work itself. Furthermore, Machotka’s intellectual trajectory, with an emphasis on the American experience as well as the meaning (for the author) of its public presentation in the Czech environment, is described. In conclusion, the significance of the edited manuscript is evaluated in terms of its theory, methodology, and contents.